Earnest [large type] - Von Kreisler, Kristin (Wheeler, Pub., 2017)
"Earnest. It's the perfect name for a sweet, eager-to-please yellow Labrador retriever. Anna and her boyfriend Jeff fall for him the minute they see those guileless eyes gazing up from behind his gate at Seattle's [Second Chance] Shelter ... During the day, Earnest keeps Anna company in her flower shop, located in a historic gingerbread Victorian on the island's main street. Anna hopes to buy and restore the house, once owned by her beloved grandmother. But when that dream is threatened by Jeff's actions, Anna's trust is shattered"--Amazon.com.